Strengthening the Character Values in the Online Learning Process - Wahyu Hidayat; Putri Dewi; Yana Nurdiana (Indonesian Journal of Islamic Education Studies (IJIES), 2021)
The application of character values ​​in the online learning process for Islamic Religious Education (PAI) subjects is a must even though it is not done face-to-face. The purpose of this study is to photograph the character values ​​taught and the challenges PAI teachers face in implementing character education in the online learning process. This type of research uses qualitative research. The sources of data in this study are teachers and students. Data were collected through interviews, documentation, and direct observation of online learning via Google Meet and WhatsApp group. The data analysis technique used is descriptive qualitative. The dominant character values ​​in online learning of Islamic religious education at SDN 114 Leppangang Pinrang are independence, love of reading, discipline, and responsibility. Some methods of implementing character education include giving advice, giving punishments and rewards in adding and subtracting task scores, and controlling student conversation in the WhatsApp group. PAI teachers have their challenges in applying student character values, one of which is not optimal control, parental concern for controlling their children, and technical problems.